Symptoms of Major Depressive Disorder and Their Impact on Psychosocial Functioning in the Different Phases of the Disease: Do the Perspectives of Patients and Healthcare Providers Differ? - Christensen, Michael Cronquist; Wong, Chiew Meng Johnny; Baune, Bernhard T. (Frontiers in Psychiatry, 2020)
This analysis was undertaken to explore the relationship between different symptoms of major depressive disorder (MDD) and psychosocial functioning from the perspectives of patients and healthcare providers (HCPs) across the different phases of the disease (acute, post-acute, and remission). Data regarding symptoms of MDD and psychosocial functioning, assessed by an adapted version of the Functioning Assessment Short Test (FAST) scale, were elicited via an online survey from 2008 patients diagnosed with MDD (based on their personal experience of the disease) and 3138 patients reported by 1046 HCPs (based on individual patient records). Correlations between patient-reported and HCP-reported MDD symptoms and impairment of psychosocial functioning were assessed by multivariate regression analysis. The population for the multivariate analysis comprised 1946 patient respondents and 3042 HCP-reported patients. Patients reported experiencinga wider range of symptoms and greater impairment of functioning than reported by HCPs across all phases of disease. At the domain level, only cognitive symptoms were found to be significantly associated with functioning during the acute phase from the perspective of patients, while from the HCPs’ perspective both mood and cognitive symptoms significantly impacted functioning during the acute phase of the disease. Significant associations were seen between mood, physical, and cognitive symptom domains and functioning in both cohorts during the post-acute and remission phases. Differences in associations between individual MDD symptoms and functioning were also observed between the two cohorts across all disease phases; in particular, HCPs found that more physical symptoms impacted functioning during remission than did patients. In summary, the results suggest that perceptions of MDD symptoms and the associations between these symptoms and functioning differ significantly between patients and HCPs across all phases of the disease. These findings further highlight the need for improved communication between patients and HCPs in order to set appropriate treatment goals and promote symptomatic and functional recovery in MDD.